Multicore simulation of power system transients - Uriarte, Fabian M. (London, United Kingdom The Institution of Engineering and Technology, 2013)
The book reviews developments in the following field: power system model; time-domain simulation; power apparatus model; data partitioning; and multithreading.
Electronic reproduction.
Keywords: Electric lines; Electric networks; Transients (Electricity); Electric power systems; Electric power transmission--Equipment and supplies; Simulation methods; Simultaneous multithreading processors; Time-domain analysis; Electronic books